Bioactivity of clitoria ternatea crude extracts against pathogenic bacteria - Liana Mohd Zulkamal; Nurul Afifah Ainna Zolhalim; Farizan Aris; Nurul Aili Zakaria; Farida Zuraina Mohd Yusof; Darah Ibrahim; Mohd Taufiq Mat Jalil (Penerbit Universiti Kebangsaan Malaysia, 2023)
Clitoria ternatea, sometimes referred to as the Asian pigeon wings blue pea, the butterfly pea, or the Darwin pea, is a Fabaceae plant species that has been shown to possess antibacterial effects against several pathogenic microbes. Hence, the present study has been carried out to access the antibacterial activity of C. ternatea flower extracted with water and methanol against pathogenic bacteria. The well and disk diffusion assays were performed to determine the antibacterial activity of C. ternatea flower extracts. The efficacy of the extracts was then evaluated via broth microdilution assay to obtain MIC and MBC values and the growth reduction assay. Meanwhile, the DPPH scavenging test was used to assess the antioxidant activity of the crude extracts. The results of the well and disc diffusion assays showed that Gram-positive bacteria were more sensitive to both extracts compared to Gramnegative bacteria. Meanwhile, the methanolic extract showed higher antibacterial activity on both Gram-positive and Gram-negative bacteria compared to the aqueous extract. The results of the MIC and MBC tests showed that the methanolic extract was bactericidal to both Gram-positive and Gram-negative bacteria. The aqueous extract, however, demonstrated bacteriostatic activity against Gram-negative bacteria and bactericidal activity solely against Gram-positive bacteria. After a 24-h exposure period, a growth reduction assay showed that the methanolic extract could suppress both Gram-positive and Gram-negative bacteria by up to 99%. Meanwhile, the aqueous extract showed an inhibition percentage value ranging from 75% to 96% after an incubation period. The aqueous extract had the lowest antioxidant activity, with an EC50 value of 87.78 µg/mL, whereas the methanolic extract had a fair amount of antioxidant activity when compared to the control (quercetin), according to the DPPH scavenging assay. The present study suggests that C. ternatea extracts as a potential antibacterial agent against pathogenic bacteria with significant antioxidant activity and this activity may be due to the presence of anthocyanin and its derivatives.